2011
DOI: 10.1111/j.1365-2567.2011.03514.x
|View full text |Cite
|
Sign up to set email alerts
|

miR‐155 modulates microglia‐mediated immune response by down‐regulating SOCS‐1 and promoting cytokine and nitric oxide production

Abstract: Summary Innate immunity constitutes the first line of defence against both external and endogenous threats in the brain, and microglia cells are considered key mediators of this process. Recent studies have shown that microRNAs (miRNAs) may play a determinant role in the regulation of gene expression during innate immune responses. The major goal of this work was to investigate the contribution of a specific miRNA – miR‐155 – to the modulation of the microglia‐mediated immune response. For this purpose, in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
253
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(267 citation statements)
references
References 32 publications
13
253
1
Order By: Relevance
“…In particular, SOCS1 is induced by IFN-␥ for autoregulation of the IFN-␥ proinflammatory response by inhibiting the JAK/STAT1 signaling pathway (41). Recent experiments in numerous cell types have revealed that miR-155 targets SOCS1 (42)(43)(44). For example, macrophages infected with an RNA virus demonstrated enhanced type I interferon production due to miR-155 targeting of Socs1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SOCS1 is induced by IFN-␥ for autoregulation of the IFN-␥ proinflammatory response by inhibiting the JAK/STAT1 signaling pathway (41). Recent experiments in numerous cell types have revealed that miR-155 targets SOCS1 (42)(43)(44). For example, macrophages infected with an RNA virus demonstrated enhanced type I interferon production due to miR-155 targeting of Socs1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA 155 (miR-155) is one of the most widely studied miRNAs in regulating inflammation (12). Silencing miR-155 ameliorates experimental autoimmune encephalomyelitis (13) and regulates inflammatory changes in astrocytes (14) and microglia (15). miR-155 plays a major role in viral infections caused by Epstein-Barr (16), Borna disease (17), and reticuloendotheliosis (18) viruses.…”
mentioning
confidence: 99%
“…Also, miR-155 expression was up-regulated in active brain lesions in multiple sclerosis where it was associated with impaired expression of CD47 in astrocytes and with consequent dysregulation of macrophage inflammatory activity [7]. Moreover, miR-155 was shown of major importance for inflammatory activity of microglia [8]. Finally, it was demonstrated essential for differentiation of Th1 and Th17 cells [9].…”
Section: Introductionmentioning
confidence: 95%